2014
DOI: 10.1371/journal.pone.0095832
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Thermodynamic Properties of Ln(III) (Ln = Eu, Sm, Dy, Nd) in 1-Butyl-3-Methylimidazolium Bromide Ionic Liquid

Abstract: The electrochemical behavior and thermodynamic properties of Ln(III) (Ln = Eu, Sm, Dy, Nd) were studied in 1-butyl-3-methylimidazolium bromide ionic liquid (BmimBr) at a glassy carbon (GC) electrode in the range of 293–338 K. The electrode reaction of Eu(III) was found to be quasi-reversible by the cyclic voltammetry, the reactions of the other three lanthanide ions were regarded as irreversible systems. An increase of the current intensity was obtained with the temperature increase. At 293 K, the cathodic pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The absence of the oxidation processes demonstrates that it is an irreversible process, as has been reported in the literature for different lanthanides in ionic liquids and organic solvent-based electrolytes. , ,,, …”
mentioning
confidence: 55%
“…The absence of the oxidation processes demonstrates that it is an irreversible process, as has been reported in the literature for different lanthanides in ionic liquids and organic solvent-based electrolytes. , ,,, …”
mentioning
confidence: 55%
“…Refractometer (Bellingham and Stanley, UK). The diffusion coefficient of Eu(III) in the aqueous and ionic liquid phases was obtained from the literature (Matsumiya et al, 2008;Rao et al, 2009;Ribeiro et al, 2011;Sengupta et al, 2012;Yang et al, 2014).…”
Section: Materials and Experimental Methodologiesmentioning
confidence: 99%
“…This is consistent with previous reports on the electrochemical behaviour of other rare earths in ILs. [22,[35][36][37][38][39] Thus, from these experiments, we observed that an irreversible reduction process occurs in the presence of dissolved Nd 3þ in [P 66614 ] [TFSI], and that this process is highly affected by the presence of moisture and the electrolyte composition.…”
Section: Resultsmentioning
confidence: 62%